Proceedings of the 4th International Conference on Modelling and Optimisation of Ship Energy Systems (TU Delft OPEN Books, 2024)
MOSES 2023 has continually served as an influential platform, fostering innovation and discussions shaping maritime energy systems’ future. Last year’s conference expanded its scope to include topics reflecting the latest technological advances impacting our industry. Key discussions focused on reducing fuel consumption, minimizing environmental impacts, and optimizing lifecycle costs in ship design and operations amidst stringent regulations and fluctuating market conditions. MOSES 2023 provided a vibrant forum for sharing innovative research, practices, and policies, and the proceedings encompass contributions from academics, industry experts, and emerging researchers, spanning diverse topics such as system modelling, optimization, control, and environmental sustainability. Highlights from the conference included a new roundtable on Data and Digitalisation, which brought together leading figures from industry and academia to explore the integration of IoT, AI, and blockchain technologies in maritime operations. This discussion focused on challenges related to data privacy, integration, and cybersecurity, underpinning the strategic importance of digital technologies in enhancing operational efficiency and safety. We invite scholars, professionals, and enthusiasts in ship energy systems to explore these proceedings, encapsulating the insights and discussions from MOSES 2023.